Do sistema tripolar-geossistema, território e paisagem à geografia transversal e de travessias: uma abordagem geográfica do distrito de Regência Augusta, Linhares-ES - Saldanha, Miguel Chaves (2018)
This study is developed based on Georges Bertrand's theory, through practices about the concepts of the GTP system (geosystem, territory and landscape) and crossing and transverse geography to an approach that integrates a geographic reading through the concepts. In order to understand the current composition of the Regência Augusta landscape, district of Linhares - ES, and to identify the main stages of landscape transformation verified, especially, throughout the 20th and 21st centuries. It also aims to add basic elements of a possible socially compromised environmental discussion. Based on reports, mappings, records, documents and research, the present study try to present the corelation between different areas of knowledge to approach the area under study in an approach that dialogues with the inherent demands of each concept of the GTP system. It was possible through this approach to classify the current landscape through the methodology of the geosystems, to compare the current and previous hydrographies to the transformations and to collaborate to the territorial perspectives that are established from the relation with the natural resources within the study area